The proliferative activity levels of each immune cell population evaluated by mass cytometry are linked to the clinical phenotypes of systemic lupus erythematosus. (23rd August 2022) - Kajihara, Akiko; Morita, Takayoshi; Kato, Yasuhiro; Konaka, Hachiro; Murakami, Teruaki; Yamaguchi, Yuta; Koyama, Shohei; Takamatsu, Hyota; Nishide, Masayuki; Maeda, Yuichi; Watanabe, Akane; Nishida, Sumiyuki; et al.
Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease, and many peripheral immune cell populations (ICPs) are thought to be altered according to the course of the disease. However, it is unclear which ICPs are associated with the clinical phenotypes of SLE. We analyzed peripheral blood mononuclear cells (PBMCs) of 28 SLE patients using mass cytometry and identified 30 ICPs. We determined the proliferative activity of ICPs by measuring the proportion of cells expressing specific markers and Ki-67 among CD45 + cells (Ki-67 + proportion). We observed an increased Ki-67 + proportion for many ICPs of SLE patients and examined the association between their Ki-67 + proportions and clinical findings. The Ki-67 + proportions of five ICPs [classical monocyte (cMo), effector memory CD8 + T cell (CD8Tem), CXCR5 − naive B cell (CXCR5 − nB), and CXCR5 − IgD − CD27 − B cell (CXCR5 − DNB)] were identified as clinically important factors. The SLE Disease Activity Index (SLEDAI) was positively correlated with cMo and plasma cells (PC). The titer of anti-DNA antibodies was positively correlated with cMo, CXCR5 − nB, and CXCR5 − DNB. The C4 level was negatively correlated with CXCR5 − DNB. The bioactivity of type I interferon was also positively correlated with these ICPs. Fever and renal involvement were associated with cMo. Rash was associated with CD8Tem and CXCR5 − DNB. On the basis of the proliferative activity among five ICPs, SLE patients can be classified into five clusters showing different SLE phenotypes. Evaluation of the proliferative activity in each ICP can be linked to the clinical phenotypes of individual SLE patients and help in the treatment strategy. Abstract : Immune-cell proliferative activity in the disease process of SLE Graphical Abstract: